2019
DOI: 10.1103/physrevb.99.085130
|View full text |Cite
|
Sign up to set email alerts
|

Electronic band structure and proximity to magnetic ordering in the chiral cubic compound CrGe

Abstract: CrGe belongs to the family of cubic B20 intermetallics. From experimental investigations by susceptibility and de Haas-van Alphen (dHvA) measurements and from calculations of its electronic band structure by densityfunctional theory (DFT), CrGe is found to form a metallic paramagnetic ground state. Combining dHvA and DFT data, a detailed picture of the Fermi surface of CrGe is provided. The proximity to a magnetic longrange ordering in CrGe is suggested from a prominent thermal magnetic susceptibility. The pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…most likely due to the magnetic breakdown or "orbital crossing" of the split Fermi surfaces in the non-centrosymmetric crystal structure, as reported in Yb 4 Sb 3 [13]. A similar phenomenon has been reported in several non-centrosymmetric metallic compounds, such as a cubic non-centrosymmetric uranium heavy-fermion U 3 Ni 3 Sn 4 [14] and a chiral cubic compound CrGe [15]. To clarify the electronic state of UPt 5 , we performed the energy band calculations using a full potential linear augmented plane wave (FLAPW) method with a local density approximation (LDA) for the 5 f -itinerant model.…”
Section: Methodssupporting
confidence: 74%
“…most likely due to the magnetic breakdown or "orbital crossing" of the split Fermi surfaces in the non-centrosymmetric crystal structure, as reported in Yb 4 Sb 3 [13]. A similar phenomenon has been reported in several non-centrosymmetric metallic compounds, such as a cubic non-centrosymmetric uranium heavy-fermion U 3 Ni 3 Sn 4 [14] and a chiral cubic compound CrGe [15]. To clarify the electronic state of UPt 5 , we performed the energy band calculations using a full potential linear augmented plane wave (FLAPW) method with a local density approximation (LDA) for the 5 f -itinerant model.…”
Section: Methodssupporting
confidence: 74%
“…There is a broad maximum arising around 100 K for x = 0 and 50 K for x = 0.0125, similar to previous report on SrCo 2 As 2 19 in which the maximum in χ(T ) was attributed to a cross-over from a coherent to an incoherent Fermi liquid state with increasing T . However, we note that this broad maximum also exists in other itinerant magnetic materials in the proximity to ferromagnetism, such as CrGe 33 . The gradual suppression with Ni substitution might suggest its close relationship with the novel magnetic phase observed in compounds with larger Ni substitution.…”
Section: A Magnetization and Magnetic Susceptibility Datamentioning
confidence: 72%
“…Considering the structural data and transport properties, it can be concluded that samples #5 ÷ #7 exhibited a high crystalline quality despite the presence of the CrGe phase in samples #5 and #6, according to XRD. Our conclusion was based on the fact that CrGe had two times higher resistivity and a very high RRR value of 260 [38]. However, no significant increase in ρ and RRR was observed for our films.…”
Section: Optical and Transport Propertiesmentioning
confidence: 49%